Location and cloning of the herpes simplex virus type 2 thymidine kinase gene. - McDougall, J K (1980)
The herpes simplex virus type 2 thymidine kinase gene has been mapped to a position colinear with the herpes simplex virus type 1 thymidine kinase gene and cloned within a 4.0-kilobase fragment in pBR 322.